2015
DOI: 10.1002/brb3.395
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in three genes are associated with hemorrhagic stroke

Abstract: BackgroundMultiligand receptor for advanced glycation end products (RAGE), osteoprotegerin, and Golgb1 genes may be implicated in atherosclerosis and vascular diseases. Single nucleotide polymorphisms (SNPs) rs1035798 in RAGE gene, rs2073617 and rs2073618 in TNFRSF11B, and rs3732410 in Golgb1 will be investigated on whether there is an association with hemorrhagic stroke (HS) in Chinese population.MethodsA total of 600 subjects including 199 HS patients and 401 controls were assayed. These samples were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 19 The interaction of matrix metalloproteinase-9 (MMP-9) gene polymorphisms may be related to the wind direction of hemorrhagic stroke. 20 APOE , 21 RAGE, TNFRSF11B, Golgb1 , 22 LPL , 23 CRP , 24 KCNK17 25 polymorphisms, and some microRNAs 26 also play a role in hemorrhagic stroke. However, other studies have failed to find a link between genetic variants and hemorrhagic stroke in different populations.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The interaction of matrix metalloproteinase-9 (MMP-9) gene polymorphisms may be related to the wind direction of hemorrhagic stroke. 20 APOE , 21 RAGE, TNFRSF11B, Golgb1 , 22 LPL , 23 CRP , 24 KCNK17 25 polymorphisms, and some microRNAs 26 also play a role in hemorrhagic stroke. However, other studies have failed to find a link between genetic variants and hemorrhagic stroke in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite results were found regarding rs1035798 (C>T), where serum RAGE and CRP levels in patients carrying homozygote CC genotype were significantly higher than in patients having mutant CT+TT genotype (Table 4). It has been hypothesized that the presence of the SNP's minor T allele interferes with splicing factor recognition [52], leading to RAGE upregulation. Our study reveals that the mutant T allele of rs1035798 (C>T) has a protective effect, that is in agreement with the other studies that showed that this variant has a protective effect in different settings [53].…”
Section: Analysis Of Risk Variables For Aspirin Resistance Using Bina...mentioning
confidence: 99%
“…31 However, the variant is relatively uncommon and even when we analyzed the Framingham offspring cohort, we were unable to identify any associations of this variant with cardiovascular disease. 32 Outside of the coding region, it is likely that variants in the promoter of RAGE may contribute to prediction for cardiovascular disease. For example, the 374T3A variant has been shown to be protective against the development of cardiovascular disease (T/A or A/A individuals) in both diabetic and nondiabetic individuals.…”
Section: Rage Polymorphisms and Cardiovascular Diseasementioning
confidence: 99%